2016
DOI: 10.1002/hon.2317
|View full text |Cite
|
Sign up to set email alerts
|

Indolent T‐ and NK‐cell lymphoproliferative disorders of the gastrointestinal tract: a review and update

Abstract: Primary gastrointestinal (GI) T-and NK-cell lymphomas are usually aggressive neoplasms associated with high morbidity and mortality. Over the past two decades, however, cases of primary GI lymphoproliferative disorders (LPDs) or lymphomas of T-or NK-cell derivation with indolent behavior have been reported. These LPDs are rare and they can be challenging to diagnose as they share clinical and pathological features with both, inflammatory disorders and aggressive T-and NK-cell lymphomas. Primary, indolent clona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…Various risk factors including genetic and molecular alterations,3, 4, 5 diet,3, 6, 7 and chronic inflammation8, 9, 10 have been linked to the development of both disorders. Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various risk factors including genetic and molecular alterations,3, 4, 5 diet,3, 6, 7 and chronic inflammation8, 9, 10 have been linked to the development of both disorders. Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 98%
“…Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract. [11][12][13][14] Although the microbiota is intimately involved in GI homeostasis and immune balance, several studies in animal models and humans with cancer incriminate bacterial-induced chronic intestinal inflammation as promoting a local environment favorable for malignant transformation, including lymphomagenesis. [11][12][13][14] Increased numbers of mucosal-adherent bacteria were observed in cats with duodenal IBD, 10 while invasive bacteria were observed within blood vessels and serosa of cats with large cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…indolent T cell lymphoproliferative disorders of the gastrointestinal tract [21][22][23][24]. Clinically, these T cell lymphomas share similar presentations with gastrointestinal symptoms such as diarrhea, abdominal discomfort, food intolerances, and weight loss [21][22][23][24]. Epitheliotropism has not been described in literature as a histologic feature of intestinal presentations of myeloid sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…This term designates clonal T‐cell proliferations involving the gastrointestinal mucosa, with a relatively indolent clinical course , . Common presenting signs are chronic diarrhea, weight loss, abdominal pain, and/or rectal bleeding.…”
Section: Intestinal T‐cell Lymphomasmentioning
confidence: 99%